Synchronous resection of 12 small pulmonary nodules guided by a noninvasive 3D printed emulation model: A case report. Issue 15 (21st June 2022) - Li, Kaidi; Ding, Ningying; Xu, Yuyang; Guo, Chenglin; Liu, Chengwu; Mei, Jiandong; Liu, Lunxu
Abstract: Localization of multiple small pulmonary nodules is the major obstacle in surgical resection. Here, we report a novel noninvasive localization technique based on a life‐size 3D printed "emulation pulmonary nodule localization model" which is simple and efficient. In the case reported here of a patient with synchronous multiple pulmonary nodules, the nodules were successfully and conveniently localized without any trauma by navigation of the emulation localization model. All 12 nodules were resected precisely and thoroughly, while normal lung tissues were considerably well preserved. Pathological examination confirmed malignancy of the major nodule and some other small nodules. Abstract : A novel localization technique based on a 3D printed "emulation pulmonary nodules localization model" was developed to guide resection of small‐sized lung nodules. It is noninvasive, convenient, time‐saving, and excels in multiple nodules. In this case of 12 synchronous multiple lung nodules, all were successfully and conveniently localized, and resected precisely, while normal lung tissues were considerably well preserved.